GEOLOGI KUARTER DATARAN PANTAI BREBES DAN SEKITARNYA, JAWA TENGAH: Respon Terhadap Peta Geologi Kuarter dan Implikasinya Terhadap Iinformasi Kondisi Geologi Holosen - Herman Mulyana; T. Chairil Basri; Herman Moechtar (Pusat Survei Geologi, 2010)
A study on Quaternary deposits in the coastal-plain of Brebes and surrounding area, Central Java, revealed eight depositional environments. They are: tidal flat (Tf), shallow marine (Sm), floodbasin (Fb), floodplain (Fb), paleochannel (Cp), Resent channel (Cr), mangrove swamp (MgS), and beach sand (B). Based on the correlation of the lateral and vertical variation of the depositional environment, tectonic activities and sea level changes were recognized. During the depositional processes, the activity of tectonic by thrust were recorded as the main factor controling global sea level fluctuation of Holocene. The result of this research is an input for the Quaternary geology study and its implications on Holocene geology conditions which is based on the Quaternary geologic mapping. The study was based on the Quaternary geologic mapping with 1:50,000 scales including an analysis of sedimentology and stratigraphy of sixty boreholes information from the coastal plain of Brebes and surrounding areas.Keywords: Quaternary geologic mapping, Holocene, coastal plain